The factors contributing to missed care and non-compliance in infection prevention and control practices of nurses: A scoping review - Lauren McCauley; Marcia Kirwan; Anne Matthews (Elsevier, 2021)
Background: There is growing concern about missed nursing care and its negative impacts on patient care and nursing and organisational outcomes. Research in the area continues to grow, with a greater focus on reliable measurement, evidence-based interventions and sensitive outcomes. The relationship between missed care and adverse patient outcomes is undeniable, including increased mortality levels, and hospital acquired infections. The link between hospital acquired infections and non-compliance with infection prevention and control guidelines is also widely acknowledged. The idea of non-compliance as an element of missed nursing care has not been closely examined and this relationship is explored in this review. Objectives: The aim of this study is to identify the shared factors related to both nurse non-compliance with infection prevention and control practices and the recognised research field of missed nursing care, here in relation to infection prevention and control. Methods: A scoping review methodology was selected to help explore and map the research evidence on non-compliance with infection prevention and control practices, and missed nursing care in relation to infection prevention and control. Results: Five key themes were identified which impact on both missed nursing care and non-compliance in the area of infection prevention and control. These included (1) Organisation of Nursing Staff and Resources; (2) Workplace Environment; (3) Nursing Care Context; (4) Managerial and Inter-Professional Relationships; and (5) Individual Nurse Factors. These shared themes underline the relationship between the concepts and suggest a shared research area. Conclusion: Missed nursing care in the area of infection prevention and control, overlaps significantly with the research area of infection prevention and control non-compliance. This suggests that rather than being approached as separate or distinct entities, these research areas should be acknowledged as related or overlapping, enabling more focused attention to reducing levels of both.Tweetable abstractMissed nursing care in the area of infection control, overlaps significantly with the research area of non-compliance with infection prevention and control guidelines.Contribution of the PaperWhat is already known about the topic?• Missed nursing care has been linked over many years with increased rates of Healthcare Associated Infection rates.• Healthcare Associated Infections can result in higher rates of morbidity and mortality, but they are largely preventable.• Infection prevention and control guidelines are designed to protect both patients and healthcare workers from infection in healthcare settings, but non-compliance with these guidelines is an on-going concern.What this paper adds?• Factors influencing missed nursing care in general, and specifically missed infection prevention and control care, are similar to factors influencing non-compliance rates with infection prevention and control guidelines.• The concepts of missed nursing care in infection prevention and control, and non-compliance with infection prevention and control guidelines are essentially the same thing and should be treated as such by nurses, researchers, and healthcare organisations. This would enable a more focused and strategic response to infection prevention and control practices, ultimately helping to reduce preventable healthcare associated infections.